Physical and Chemical Quality of Cow Feces Organic Fertilizer Produced by the Addition of Different Starters - V. Pastawan; E. Baliarti; H. Maulana; N. A. Fitriyanto (Jurnal Sain Peternakan Indonesia, 2023)
The study aims to know the effect of different starters on the quality production of organic fertilizer. Three kinds of starters, EM-4 (P1), BM-4 (P2), and Petroganic (P3), were used in this study. The quality of organic fertilizer with a starter for the 28th day of composting was evaluated by physical and chemical parameters in triplicates. Based on the results, we showed the physical parameters of treatment compost P1, P2, and P3 are blackish brown, didn’t smell of stool, and are crumbly textured. The chemical parameters showed the content of C-organic from the treatments was 42.51%, 39.19%, and 35.74%, respectively, at the end of the composting process, while total nitrogen content was 4.71%, 9.47%, and 5.77%. The C/N ratio of each treatment, P1, P2, and P3, was 9.02, 4.17, and 6.20, while the total phosphor content was 0.092%, 0.15%, and 0.13%, respectively. Next, the total potassium content was 0.69%, 0.79%, and 0.77%, respectively, at the end of the composting process. The addition of different types of starters did not affect physical and chemical quality. In conclusion, EM-4, BM-4, and Petroganik can be used as alternative starters in producing organic fertilizer.